Avian Influenza A Virus Polymerase Can Utilize Human ANP32 Proteins To Support cRNA but Not vRNA Synthesis - Olivia C. Swann; Amalie B. Rasmussen; Thomas P. Peacock; Carol M. Sheppard; Wendy S. Barclay (mBio, 2023)
ABSTRACT Host restriction limits the emergence of novel pandemic strains from the influenza A virus avian reservoir. For efficient replication in mammalian cells, the avian influenza RNA-dependent RNA polymerase must adapt to use human orthologues of the host factor ANP32, which lack a 33-amino-acid insertion relative to avian ANP32A. Here, we find that influenza polymerase requires ANP32 proteins to support both steps of genome replication: cRNA and vRNA synthesis. However, avian strains are only restricted in vRNA synthesis in human cells. Therefore, avian influenza polymerase can use human ANP32 orthologues to support cRNA synthesis, without acquiring mammalian adaptations. This implies a fundamental difference in the mechanism by which ANP32 proteins support cRNA versus vRNA synthesis. IMPORTANCE To infect humans and cause a pandemic, avian influenza must first adapt to use human versions of the proteins the virus hijacks for replication, instead of the avian orthologues found in bird cells. One critical host protein is ANP32. Understanding the details of how host proteins such as ANP32 support viral activity may allow the design of new antiviral strategies that disrupt these interactions. Here, we use cells that lack ANP32 to unambiguously demonstrate ANP32 is needed for both steps of influenza genome replication. Unexpectedly, however, we found that avian influenza can use human ANP32 proteins for the first step of replication, to copy a complementary strand, without adaptation but can only utilize avian ANP32 for the second step of replication that generates new genomes. This suggests ANP32 may have a distinct role in supporting the second step of replication, and it is this activity that is specifically blocked when avian influenza infects human cells.